Theoretical predictions of doping strategies improving the transport properties of Li2SnO3 - Mut-Benítez, Rafael Francisco; Soto, E.; Tho-Nguyen, Minh; A. Zulueta, Yohandys (Revista Cubana de Química, 2022)
Nowadays, one of the primary worldwide challenges is the replacement of conventional fossil fuels by different renewable energy sources. The search for suitable solutions is getting more urgent in view of the severe consequences of the climate change the distribution of energy resources. Lithium stannate (Li2SnO3) is one of the battery material used as electrode and inorganic solid electrolyte. In this work, advanced atomistic simulations were performend to disclose the defect energetics behavior and large scale transport properties of pristine and metal doped Li2SnO3. The results of defect energetics computations show that divalent dopants occupies the Li site, leading to Li vacancy formation is a viable incorporation mechanism. In contrast, trivalent dopants have a strong energetic preference for doping at the Sn site, with charge compensation from Li interstitial formation. The results of molecular dynamics simulations disclose improvements of transport properties of Li2SnO3 upon doping strategies are observed.